Development and Implementation of an Influenza Point-Of-Care Testing Service in a Chain Community Pharmacy Setting - Rachel Hardin; Pheli Roberts; Brooke Hudspeth; Angela Tracy; Lauren Baldwin; Michael Raque; Clark D. Kebodeaux (MDPI AG, 2020)
Point-of-care testing is becoming increasingly commonplace in community pharmacy settings. These tests are often used in the management of chronic disease, such as blood sugar, hemoglobin A1c and lipid levels, but can also be used for acute conditions such as influenza infection and group A streptococcus pharyngitis. When used for these acute infections, point-of-care tests can allow for pharmacist-initiated treatment. In this study, an influenza point-of-care testing service was developed and implemented in a chain community pharmacy setting and a retrospective review was conducted to assess the service. Of patients tested, 29% tested positive for influenza A and/or B; 92% of patients testing positive received a prescription as a result. While health insurance cannot be billed for the service due to current pharmacy reimbursement practices, this did not appear to negatively affect patient willingness to participate. As point-of-care testing services become more commonplace in community pharmacy settings, patient awareness will similarly increase and allow for more widespread access to acute outpatient care.